Agrobacterium-Mediated Transient Gene Expression in Developing Ricinus communis Seeds: A First Step in Making the Castor Oil Plant a Chemical Biofactory - Sánchez-Álvarez, Alfonso; Ruíz-López, Noemí; Moreno-Pérez, Antonio Javier; Martínez-Force, Enrique; Garcés, Rafael; Salas, Joaquín J. (Frontiers in Plant Science, 2019)
The castor oil plant represents a promising platform to produce oils with industrial applications. However, its use in biotechnology is limited by the absence of a well-established procedure to transform it, and a poor understanding of gene regulation and promoter use in this species. As such, a quick method has been developed to express proteins or hairpin-RNA in this plant, a method based on the direct injection of Agrobacterium into the developing endosperm of castor oil fruit, enabling different constructs and promoters to be tested. This method produces a high rate of transformation and a good proportion of viable seeds that express reporter genes for up to 20 days after imbibition (DAI). Gene expression under the control of different promoters was tested by RT-qPCR and by directly assaying the activity of the GUS reporter gene, which proved to be strongest when driven by the glycinin promoter. Constructs expressing a fatty acid elongase from Lesquerella fendlery were tested, the expression of which provoked an important increase in the lesquerolic acid in the castor oil endosperm at 5 and 10 DAI, although this fatty acid did not accumulate significantly in the final mature seeds. The nature of this response could reflect the poor availability of substrates for this enzyme. In the light of this data, the potential of this technique to test promoters and different constructs in castor oil plants and other oilseeds is discussed.